Purpose, subject matter and objectives of forensic medicine - O. S. Moiseyenko (Bulletin of Kharkiv National University of Internal Affairs)
It has been established that forensic medicine is a branch of medicine that deals with the application of medical knowledge and methods to resolve legal issues, in particular those related to death, injury and other types of violence. The main purpose of forensic medicine is to examine the bodies of the dead or injured in order to determine the cause of death or injury, as well as to determine the possible criminal element in the act. To do this, forensic physicians use methods of body examination, evidence collection and expert analysis.